Kisspeptin treatment improves fetal-placental development and blocks placental oxidative damage caused by maternal hypothyroidism in an experimental rat model - Santos, Bianca Reis; dos Anjos Cordeiro, Jeane Martinha; Santos, Luciano Cardoso; Barbosa, Erikles Macedo; Mendonça, Letícia Dias; Santos, Emilly Oliveira; de Macedo, Isabella Oliveira; de Lavor, Mário Sergio Lima; Szawka, Raphael Escorsim; Serakides, Rogeria; Silva, Juneo Freitas (Frontiers in Endocrinology, 2022)
Maternal hypothyroidism is associated with fetal growth restriction, placental dysfunction, and reduced kisspeptin/Kiss1R at the maternal-fetal interface. Kisspeptin affects trophoblastic migration and has antioxidant and immunomodulatory activities. This study aimed to evaluate the therapeutic potential of kisspeptin in the fetal-placental dysfunction of hypothyroid Wistar rats. Hypothyroidism was induced by daily administration of propylthiouracil. Kisspeptin-10 (Kp-10) treatment was performed every other day or daily beginning on day 8 of gestation. Feto-placental development, placental histomorphometry, and expression levels of growth factors (VEGF, PLGF, IGF1, IGF2, and GLUT1), hormonal (Dio2) and inflammatory mediators (TNFα, IL10, and IL6), markers of hypoxia (HIF1α) and oxidative damage (8-OHdG), antioxidant enzymes (SOD1, Cat, and GPx1), and endoplasmic reticulum stress mediators (ATF4, GRP78, and CHOP) were evaluated on day 18 of gestation. Daily treatment with Kp-10 increased free T3 and T4 levels and improved fetal weight. Both treatments reestablished the glycogen cell population in the junctional zone. Daily treatment with Kp-10 increased the gene expression levels of Plgf, Igf1, and Glut1 in the placenta of hypothyroid animals, in addition to blocking the increase in 8-OHdG and increasing protein and/or mRNA expression levels of SOD1, Cat, and GPx1. Daily treatment with Kp-10 did not alter the higher protein expression levels of VEGF, HIF1α, IL10, GRP78, and CHOP caused by hypothyroidism in the junctional zone compared to control, nor the lower expression of Dio2 caused by hypothyroidism. However, in the labyrinth zone, this treatment restored the expression of VEGF and IL10 and reduced the GRP78 and CHOP immunostaining. These findings demonstrate that daily treatment with Kp-10 improves fetal development and placental morphology in hypothyroid rats, blocks placental oxidative damage, and increases the expression of growth factors and antioxidant enzymes in the placenta.